A formal proof of the factor price equalization theorem (2004)
This paper provides a formal proof of the Factor Price Equalization Theorem within the Heckscher Ohlin model derived by Ronald W. Jones in "The Structure of Simple General Equilibrium Models" (1965), where formal proof is provided for the Heckscher Ohlin, Stolper Samuelson and Rybczynski Theorems.